Quiet New Particle Formation in the Atmosphere - Kulmala, Markku; Junninen, Heikki; Dada, Lubna; Salma, Imre; Weidinger, Tamás; Thén, Wanda; Vörösmarty, Máté; Komsaare, Kaupo; Stolzenburg, Dominik; Cai, Runlong; Yan, Chao; Li, Xinyang; et al. (Frontiers in Environmental Science, 2022)
Atmospheric new particle formation (NPF) has been observed to take place in practice all around the world. In continental locations, typically about 10‒40 % of the days are so-called NPF event days characterized by a clear particle formation and growth that continue for several hours, occurring mostly during daytime. The other days are either non-event days, or days for which it is difficult to say whether NPF had occurred or not. Using measurement data from several locations (Hyytiälä, Järvselja, and near-city background and city centre in Budapest), we were able to show that NPF tends to occur also on the days traditionally characterized as non-event days. One explanation is the instrument sensitivity towards low number concentrations in the sub-10 nm range, which usually limits our capability to detect such NPF events. We found out that during such days, particle formation rates at 6 nm were about 2‒20% of those observed during the traditional NPF event days. Growth rates of the newly formed particles were very similar between the traditional NPF event and non-event days. This previously overlooked phenomenon, termed as quiet NPF, contributes significantly to the production of secondary particles in the atmosphere.